2019
DOI: 10.1080/20008198.2019.1661814
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between distinctive patterns of emotion regulation, trauma exposure and psychopathology among refugees resettled in Australia: a latent class analysis

Abstract: Background: Emotion regulation difficulties are common among individuals from refugee backgrounds. Little is known, however, about whether there are specific patterns relating to the types of emotion regulation strategies commonly employed by refugees, nor how this relates to psychopathology. Moreover, wider literature on emotion regulation has primarily focused on examining specific emotion regulation strategies in isolation, rather than patterns of emotion regulation across multiple strategies. Objective: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(32 reference statements)
1
10
1
1
Order By: Relevance
“…However, when considering certain diseases, this may vary over time, with a higher prevalence of hypertension, diabetes, obesity, and cognitive impairment in migrants (Markines and Gerst 2011 ; Markides & Rote, 2015 ). This phenomenon also occurs with regard to mental health (Honkaniemi et al, 2020 ), such as depression, anxiety, PTSD, emotional dysregulation, and psychological distress (Bhugra & Jones, 2001a , 2001b ; Carroll et al, 2020 ; Honkaniemi et al, 2020 ; Kuo 2014 ; Specker & Nickerson, 2019 ; Virgincar et al, 2016 ). In this paradox, although residence time is considered an important element for health, as mentioned, there is conflicting evidence as regards mental health (Dunn and Dyck 2000 ; Laroche, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when considering certain diseases, this may vary over time, with a higher prevalence of hypertension, diabetes, obesity, and cognitive impairment in migrants (Markines and Gerst 2011 ; Markides & Rote, 2015 ). This phenomenon also occurs with regard to mental health (Honkaniemi et al, 2020 ), such as depression, anxiety, PTSD, emotional dysregulation, and psychological distress (Bhugra & Jones, 2001a , 2001b ; Carroll et al, 2020 ; Honkaniemi et al, 2020 ; Kuo 2014 ; Specker & Nickerson, 2019 ; Virgincar et al, 2016 ). In this paradox, although residence time is considered an important element for health, as mentioned, there is conflicting evidence as regards mental health (Dunn and Dyck 2000 ; Laroche, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In migrants residing in the Netherlands, suppression under certain contexts (e.g., positive and negative emotional manifestations during interactions with family and unknown people) was found to be a significant mediator of higher emotional suppression and low well-being (Stupar et al 2014 ). In Australia, refugees with emotion regulation difficulties reported greater PTSD symptoms and emotion dysregulation strategies compared to emotionally regulated refugees (Specker & Nickerson, 2019 ). Emotion regulation can also be conceptualized as a transdiagnostic factor because of its associations and predictive ties to depression, PTSD symptoms, anxiety, and insomnia in Afghan refugees exposed to trauma (Koch et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This association between greater ER variability and better psychological functioning is consistent with past survey-based research. Eftekhari et al (2009) and Specker and Nickerson (2019) both found that more variable ER repertoires-among female undergraduate students and adult refugees, respectively-were associated with lower PTSD symptom severity. As the first experimental investigation of ER repertoires, our study additionally found that greater ER variability was associated with lower distress immediately following trauma-related stressors.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, previous research with refugees or people who were exposed to traumatic situations indicates that the use of emotion suppression strategies predicts the development of post-traumatic symptoms and increases the likelihood of developing mental problems in the future [58]. Furthermore, some studies suggest that emotion suppression is an aggravating factor in the effects of traumatic experience [59].…”
Section: Discussionmentioning
confidence: 99%